Tris(2-ethylhexyl) phosphate induces cytotoxicity in TM3 Leydig cells by modulating autophagy and endoplasmic reticulum stress - Zhang, Wenqiao; Song, Yali; Yi, Letai; Ou, Jinhuan; Chen, Junhui; Zhang, Wei; Wen, Qinglian; Yang, Chuanbin; Wang, Jigang (Ecotoxicology and environmental safety, 2024)
Tris (2-ethylhexyl) phosphate (TEHP) is a frequently used organophosphorus flame retardant with significant ecotoxicity and widespread human exposure. Recent research indicates that TEHP has reproductive toxicity. However, the precise cell mechanism is not enough understood. Here, by using testicular mesenchymal stromal TM3 cells as a model, we reveal that TEHP induces apoptosis. Then RNA sequencing analysis, immunofluorescence, and western blotting results show that THEP inhibits autophagy flux and enhances endoplasmic reticulum (ER) stress. Moreover, the activation of the ER stress is critical for TEHP-induced cell injury. Interestingly, TEHP-induced ER stress is contributed to autophagic flux inhibition. Furthermore, pharmacological inhibition of autophagy aggravates, and activation of autophagy attenuates TEHP-induced apoptosis. In summary, these findings indicate that TEHP triggers apoptosis in mouse TM3 cells through ER stress activation and autophagy flux inhibition, offering a new perspective on the mechanisms underlying TEHP-induced interstitial cytotoxicity in the mouse testis. •TEHP induces apoptosis in TM3 Leydig cells.•TEHP inhibits autophagy flux.•TEHP activates ER stress.•Both autophagy dysfunction and ER stress contribute to TEHP-induced cell death.